THE INFLUENCE OF MOTHER TONGUETO STUDENTS’ PRONUNCIATION AT ENGLISH EDUCATIONAL PROGRAM (TBI) STAIN PADANGSIDIMPUAN (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2013)
Abstract Based on fact of the influence of mother tongue to students’ pronunciation at English Educational Program (TBI) STAIN Padangsidimpuan the researcher focused on vowel and consonant which is produced by Angkola Students or the students who used Batak Angkola as their daily language.In this research, the researcher wanted to find out about the influence of mother tongue to students pronunciation. The respondents of research was the students of English Educational Program TBI who used Batak Angkola language as their daily language, they were 12 students and almost 80% students used Batak Angkola as their daily language. As the instrument for collecting data the researcher used the test. The researcher made transcribing data for analyzing data.In this occasion, all respondents pronunced the test depend on their daily pronunciation. And they dominantly used the English feature of pronunciation that have a big similarity with the feature of pronunciation of Batak Angkola.And the last mother tongue had a significant influence, but actually mother tongue also not a big problem in Angkolas’ students in their pronunciation. And the students have to drill their pronunciation, so that they can pronunce the word as well as the standard of receive pronunciation.Key Words: mother tongue, pronunciation